Design of a Standardized Inter Satellite Optical Wireless Communication (IsOWC) System with Minimum Input Power. (2016) - Sarath Ganga, S.; Asha, R.S.; Shaija, P.J.
Abstract: This paper proposes a novel method for low power communication between two Low Earth Orbiting satellites. The IsOWC system is designed for minimum input power of 27.02 dBm and -7.6 dBm, at 2.5Gbps. A standardized system for a distance of 5000km and wavelength 1550nm is designed and its performance is analysed by varying the modulation schemes and filters. A Square root (SQRT) transfer function module (SRm) is used to compensate the square-law characteristic of the photodiode. By using SRm in the system 67% increment in system efficiency is observed. The optimized performance is obtained by using NRZ scheme and Bessel filter. Highest Q factor of 6.70dB and 6.72dB are obtained for simulation with NRZ scheme and Bessel filter respectively, with minimum BER 10 -12.